The effect of Functional Strength Exercises on the Development of Some Working Muscles in Youth Artistic Gymnastics for Men - Younis, Frial (Journal of Physical Education, 2016)
The aim of the research was to design functional strength exercise to develop some working muscles capacities as well as identifying the effects of functional strength exercises on working muscles. The researchers used the experimental method and the subjects were (6) youth gymnasts. The researchers conducted three pilot studies using EMG to catch Bluetooth signals to display them on a laptop and save them on Myo research program. The researchers conducted the experiments from 20/7/2016 – 25/11/2015. The data was collected and treated using proper statistical operations to come up with the results. The researchers concluded that functional strength exercises develop maximum muscular strength in youth gymnasts. The researcher recommended depending on functional strength exercises when training youth gymnasts and equipping training gyms with functional strength equipments due to their positive effect in developing physical and skillful performance.